Alterations of the Hippocampal Networks in Valproic Acid-Induced Rat Autism Model - Bódi, Veronika; Májer, Tímea; Kelemen, Viktor; Világi, Ildikó; Szűcs, Attila; Varró, Petra (Frontiers in Neural Circuits, 2022)
Autism Spectrum Disorder (ASD) is one of the most frequently diagnosed neurodevelopmental disorders, characterized among others by impairments in social interactions and repetitive behavior. According to one of the leading hypotheses about its origin, ASD is caused by the imbalance of excitatory and inhibitory circuit activity. ASD-related morphological and functional changes can be observed in several brain regions i.e. in the prefrontal cortex and the hippocampus. It is well-established that prenatal valproic-acid (VPA) exposure of rats on day 12.5 leads to neurodevelopmental alterations with autism-like clinical and behavioral symptoms. The aim of this study was to investigate potential changes in the excitability of neuronal networks and individual neurons of the hippocampus elicited by prenatal VPA treatment. As there are marked sex differences in ASD, offspring of both sexes were systematically tested, using two different age groups, to elucidate eventual differences in neurodevelopment after VPA treatment. Excitatory connections and long-term synaptic plasticity as well as intrinsic excitability of CA1 pyramidal cells were examined. Pregnant female Wistar rats received saline or 500 mg/kg VPA i. p. on gestation day 12.5. Brain slices of 6-week-old and 3-month-old offspring were investigated using extra- and intracellular electrophysiological techniques. Field potential- and whole-cell patch clamp recordings were carried out to measure network excitability and single cell activity in the CA1 region hippocampus. Enhanced excitability of hippocampal networks was detected in the 6-week-old VPA-treated male rats; however, this change could not be observed in 3-month-old males. Intrinsic excitability of single neurons, however, was increased in 3-month-old males. In 6-week-old treated females, the most prominent effect of VPA was an increase in voltage sag, to a similar degree to the neurons of the older age group. In 3-month-old females, a network excitability increase could be demonstrated, in a lesser degree than in younger males. . It can be concluded, that VPA treatment had diverse effects on hippocampal excitability depending on the sex and the age of the animals. We found that certain alterations manifested in 6-week-old rats were compensated later, on the other hand, other changes persisted until the age of 3 months.